Administracyjnoprawne aspekty wykonywania zawodu psychologa w dobie zmieniających się oczekiwań dotyczących usług społecznych – wybrane zagadnienia - Wilkowska-Kołakowska, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
W obliczu dynamicznych zmian w oczekiwaniach społecznych wobec usług psychologicznych, prawna regulacja zawodu psychologa w Polsce nabiera szczególnego znaczenia. Planowana na pierwszy kwartał 2026 roku nowa ustawa o zawodzie psychologa oraz samorządzie zawodowym psychologów ma na celu kompleksowe uregulowanie tej profesji, dostosowując ją do współczesnych realiów i potrzeb społeczeństwa. Celem artykułu jest analiza wybranych regulacji prawnych przewidywanych w projekcie ustawy w zakresie zasad uzyskiwania uprawnień zawodowych w zawodzie psychologa oraz zadań samorządu zawodowego, które są najistotniejsze dla określenia ich wpływu na ochronę praw pacjentów. W wyniku przeprowadzonych badań stwierdzono, że dwuetapowa weryfikacja kwalifikacji psychologów stanowi niewątpliwie krok w dobrym kierunku, jeżeli chodzi o realizację podstawowego celu regulacji zawodu zaufania publicznego, jakim jest ochrona interesu społecznego wyrażającego się w ochronie zdrowia psychicznego. Administracyjnoprawna regulacja zawodu psychologa w drodze utworzenia samorządu zawodowego również przyczyni się do poprawy jakości świadczonych usług psychologicznych, pod warunkiem takiego jego ukształtowania i wyposażenia w kompetencje, które pozwoliłoby pogodzić realizację interesów tej grupy zawodowej z interesem publicznym.

In the face of dynamic changes in social expectations towards psychological services, the legal regulation of the profession of psychologist in Poland is becoming particularly important. Planned for the first quarter of 2026, the new law on the profession of psychologist and the professional self-government of psychologists aims to comprehensively regulate this profession, adapting it to contemporary realities and the needs of society. The aim of the research is to analyse selected legal regulations provided for in the draft bill regarding the rules for obtaining professional qualifications in the profession of psychologist and the tasks of the professional self-government, which are most important for determining their impact on the protection of patients' rights. The research conducted has shown that the two-stage verification of psychologists' qualifications is undoubtedly a step in the right direction in terms of achieving the fundamental objective of regulating a profession of public trust, which is to protect the public interest as expressed in the protection of mental health. The administrative and legal regulation of the profession of psychologist through the creation of a professional self-governing body will also contribute to improving the quality of psychological services provided, on condition that it is structured and equipped with competences that would allow the interests of this professional group to be reconciled with the public interest.
Administrative and legal aspects of practicing as a psychologist in times of changing expectations regarding social services – selected issues
Keywords: zawód psychologa; samorząd zawodowy; kwalifikacje zawodowe; zmiany legislacyjne; administracyjnoprawna regulacja; psychologist profession; self-governing body; professional qualifications; legislative changes; administrative and legal regulation